Office exercise training to reduce and prevent the occurrence of musculoskeletal disorders among office workers: a hypothesis - Shariat, Ardalan; Mohd Tamrin, Shamsul Bahri; Arumugam, Manohar; Danaee, Mahmoud; Ramasamy, Rajesh (Penerbit Universiti Sains Malaysia, 2016)
Pain in specific areas of the body (including the lower back, neck, and shoulders) due to extended periods of sitting and inactivity is the most widespread musculoskeletal disorder worldwide and has consequences that are both socio-economic and personal. This condition is particularly prevalent in industrialised countries, affecting roughly 70% to 80% of adults at some point in their lives; approximately 1% of the U.S. population is chronically disabled by this type of pain disorder. A practical way to reduce the prevalence of musculoskeletal pain among office workers would have a significant positive impact. More work is required to develop a package of exercises designed to prevent and treat musculoskeletal pain in office workers. Such a package would be preferable to pharmacological treatments, which can have undesirable side effects. The main objective of this package would be to increase the flexibility and strength of trunk muscles in order to decrease the soreness, pain, and degree of discomfort. In this article, we introduce our proposed package of exercises, which are based on guidelines issued bythe American College of Sports Medicine.